Developmental and polyamine metabolism alterations in Rhinella arenarum embryos exposed to the organophosphate chlorpyrifos - Sotomayor, Veronica (2012)
Organophosphorus pesticides (OPs) are widely applied in the Alto Valle of Río Negro and Neuquén, Argentina, due to intensive fruit growing. Amphibians are particularly sensitive to environmental pollution, and OPs may transiently accumulate in ponds and channels of the region during their reproductive season. Organophosphorus pesticide exposure may alter amphibian embryonic development and the reproductive success of autochthonous species. In the present study, embryos of the common toad Rhinella arenarum were employed to assess developmental alterations and to study polyamine metabolism, which is essential to normal growth, as a possible target underlying the effects of the OP chlorpyrifos. As the duration of chlorpyrifos exposure increased and embryonic development progressed, the median lethal concentration (LC50) values decreased, and the percentage of malformed embryos increased. Developmental arrest was also observed and several morphological alterations were recorded, such as incomplete and abnormal closure of the neural tube, dorsal curvature of the caudal fin, reduction of body size and caudal fin length, atrophy, and edema. An early decrease in ornithine decarboxylase (ODC) activity and polyamine levels was also observed in embryos exposed to chlorpyrifos. The decrease in polyamine contents in tail bud embryos might be a consequence of the reduction in ODC activity. The alteration of polyamine metabolism occurred before embryonic growth was interrupted and embryonic malformations were observed and may be useful as a biomarker in environmental studies.